DEVELOPMENT OF THE NETWORK OF SOCIAL SHOPS BASED ON FRANCHISE - D. Wafin; E. Hmelchenko (Вестник университета)
Franchising is a long-term commercial concession agreement between companies, implying the transfer by one company of another of its right to use certain intellectual property objects within the specified territory. Under the franchise agreement, the franchisor grants to the user (franchisee) the entire complex of intellectual property rights belonging to him (one or several trademarks, company name, inventions and industrial designs, know-how, copyrighted works). Using modern marketing technologies, carrying out in-depth analysis, studying foreign experience will help to form a concept that will eventually bear fruit